Smoothing the energy transfer pathway in quasi-2D perovskite films using methanesulfonate leads to highly efficient light-emitting devices - Lingmei Kong; Xiaoyu Zhang; Yunguo Li; Haoran Wang; Yuanzhi Jiang; Sheng Wang; Mengqing You; Chengxi Zhang; Ting Zhang; Stephen V. Kershaw; Weitao Zheng; Yingguo Yang; et al. (Nature Communications, 2021)
Owing to large exciton binding energy, quasi-2D perovskite is promising for light-emitting application, yet inhomogeneous phases distribution limits the potential. Here, the authors improve the performance by using MeS additive to regulate the phase distribution and to reduce defect density in the films.